Upaya Yang Dilakukan Orang Kristen Dalam Meningkatkan Kerohanian - Septiniar Laoli; Martin Putra Hura (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2024)
The reasons why Christians find it difficult to mature spiritually include: 1) slowness to listen, 2) feeling that they already know, 3) hardening their hearts against God's words, 4) believing because they only want to get blessings, and 5) their first love for God has faded. The purpose of this research is to study and understand the efforts made by Christians in improving their spiritual life and the benefits are to provide better insight and understanding of effective practices in improving the spiritual life of Christians. Furthermore, the research method used by this author is a descriptive qualitative research method through library research related to